Investigating the impact of stormwater fouling on polysulfone ultrafiltration membranes modified with deep eutectic solvents - Yousef Elhamarnah (17869382) (2023)
In this study, we evaluate the performance of modified polysulfone (PSF) ultrafiltration (UF) membranes, which incorporate deep eutectic solvents (DES), in treating stormwater laden with natural organic matter e.g. chemical oxygen demand (COD) and total suspended solids (TSS). We also aim to understand how these organic substances, e.g. COD, TSS, from the water source contribute to the fouling of the synthesized membranes. PSF membranes were synthesized using a non-solvent induced phase separation technique and integrated with varying concentrations of ChCl:FR (Choline Chloride: D-(−)-Fructose) 1:1 DES. The surface and porous structures of the membranes were characterized through Fourier-transform infrared spectroscopy (FTIR), atomic force microscopy (AFM), contact angle measurements, scanning electron microscopy (SEM), and mechanical testing. The UF performance of these membranes was assessed and compared with different commercially available UF flat sheet membranes in terms of pure water permeability and antifouling behavior against collected stormwater from a sedimentation pond. Furthermore, the study evaluated the quality of the permeate based on parameters such as COD, turbidity, TSS, pH, and conductivity and compared the permeate quality of a pilot-scale ceramic UF membrane unit. The findings indicate that the inclusion of DES in the polysulfone membrane structure enhances the membranes' antifouling properties and permeability. This research offers valuable insights into the role of DES in the formation of polysulfone UF membranes and their potential for practical use e.g. sedimented stormwater. Other Information Published in: Journal of Water Process Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jwpe.2023.104362